Geopolymer concrete columns subjected to axial load and biaxial bending - Rahman, Muhammad Motiur (Curtin University, 2013)
This thesis focuses on the behaviour of fly ash based geopolymer concrete columns under axial load and biaxial bending. Tests showed that failure load of columns increased with the increase of concrete compressive strength and longitudinal reinforcement ratio, and decreased with the increase of load eccentricity. Use of the Bresler’s reciprocal load formula with an iterative procedure for slender columns in uniaxial bending conservatively predicted the strength of the test columns.